Analisis Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Peserta Didik Kelas 1 di SD Negeri Cipaku 2 pada Mata Pelajaran Pendidikan Pancasila - Supardi U.S; Leny Hidayanti (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to examine the application of varied learning methods in Pancasila Education subjects in grade 1 of SD Negeri Cipaku 2 Bogor City. The research was conducted with a descriptive approach through observation, questionnaire distribution, and document analysis. The results show that the application of differentiation strategies—including content, processes, and products—is able to increase students' enthusiasm and involvement in learning activities. Teachers first conduct diagnostic tests to map students' learning interests and needs before developing appropriate teaching methods. The students' response to learning was very positive, and the teacher felt that the strategies implemented successfully met their needs and interests. The main challenge in differentiated learning is to change the perception of students who think that the learning process is uniform. To overcome this, teachers provide an understanding that different methods are not forms of discrimination, but rather ways to adapt learning to individual needs. These findings indicate that the differentiation approach is effective in increasing the effectiveness of learning and student involvement in understanding Pancasila Education.